Kriminalisasi Korban KDRT Ditinjau dalam Perspektif Viktimologi (Studi Kasus: Putusan Nomor 256/Pdt.P/2021/PN Kwg) - Tsania Fathhiyya Medina; Kevin Jonathan Sihombing; Bon Bon Yesita Putri; Rizky Maulana; Refian Dela Angelina; M. Rival Revana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Domestic violence is basically formulated as any form of behavior that causes physical and psychological suffering to someone who is within the scope of the household. Records on domestic violence show a consistent and significant increase in the number of cases. Criminalization of domestic violence victims often occurs such as the case experienced by Valencya, she was reported by her husband until finally the Prosecutor charged Valencya with violating the article 45 ayat (1) junto Pasal 5 huruf Undang-Undang Nomor 23 tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga (UUPKDRT). The purpose of this study is to analyze the prosecutor's demands in Valencya's case study and examine the concept of legal protection for criminalization of victims of domestic violence. This research uses a case approach and a statutory approach. The data obtained are analyzed descriptively. The findings of this study show that law enforcement uses the domestic violence law to criminalize women victims of domestic violence. But with all considerations, the JPU finally dropped the one-year prison sentence in Valencya's case to acquittal. Therefore, awareness of the importance of consistency in law enforcement is needed, especially in handling domestic violence cases in order to decide appropriately and in accordance with applicable law. The rights of victims of domestic violence are rights obtained by every Indonesian citizen, which is affirmed in article 3 of the Law on Domestic Violence. This research is for all walks of life. However, in practice the rights of victims of domestic violence have not been fulfilled in their entirety. The number of victims of domestic violence who, after undergoing recovery, have to return home and receive violence again from their husbands, this is of course a very crucial problem. And the criminalization of domestic violence victims is an issue that must be considered. The purpose of this study is to examine the criminalization of victims of domestic violence.